The harms of remedial discretion - Leckey, Robert (International Journal of Constitutional Law, 2016)
This article raises a dissenting voice against the widespread scholarly view that discretion in remedying legislative infringement of rights can be dialogic, gentle, and cooperative. It focuses on delayed and prospective orders under the Canadian Charter of Rights and Freedoms and the South African Bill of Rights. Scholars have neglected remedial discretion’s significant negative consequences. It harms litigants and other right bearers, potentially producing perverse systemic effects. In particular, keeping a rights-infringing criminal prohibition temporarily in force is unlikely to achieve legal certainty and risks undermining the rule of law. Far from being restrained and deferential, remedial discretion increases the reach of judicial decision-making and enables judges to shape new law more boldly. The widespread exercise of remedial discretion calls for refashioning the conception of a bill of rights’ place in a supreme constitution. If delayed or prospective remedies are sometimes appropriate, they are not something to celebrate.